DETERMINAN AKUNTABILITAS PENGELOLAAN KEUANGAN DESA (STUDI EMPIRIS PADA DESA DI KABUPATEN DEMAK) - Valentina Adventa Khesa Widhastama; Jaeni Jaeni (JURNAL ILMIAH EDUNOMIKA, 2024)
The result of the research has the aim of impacting the determinants of accountability in village’s financial management in Demak Regenc). Research testing uses causal testing (hypothesis testing) because it uses hypotheses for tests carried out between variables. The sample on the researches was taken just use purposive sampling of 80 respondents. The data on this research using method uses quantitative data and primary data. That type use research on data uses validity test methods, reliability of tests, multiple linear regression for analysis, classic assumption tests (normality, multicollinearity and heteroscedasticity) and hypothesis tests processed using SPSS 26. The results of task are presentation of financial statements is not significant and negative. That research Internal Control System the results are significant and positive. The results of Community Participation are not significant and positive. The Village Apparatus Competency results are significant and positive in. Meanwhie results of Financial Report Accessibility are insignificant and negative. Keywords : Financial Statement Accessibility, Internal of Control System, ,Village Financial Management Accountability